Characters expression in rubber tree and obtainment of clones with production and resistance to south american leaf blight - Valois, Afonso Celso Candeira (Pesquisa Agropecuaria Brasileira, 2014)
In general terms, this report shows a research methodology with rubber tree (Heavea spp) for obtainment of produtive clones with permanent resistance to fungi Microcyclus ulei. It also shows aspects in relation to major influence of genes in characters and their relations with attack of pest and disease and atual level of knowledgement of host x guest x environment interaction in relation to the rubber tree South American Leaf Blight.